2021
DOI: 10.3390/pharmaceutics13111743
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic ZnO Nanoparticles Synthesized from Origanum vulgare Abrogates Quorum Sensing and Biofilm Formation in Opportunistic Pathogen Chromobacterium violaceum

Abstract: This study presents an inexpensive, eco-friendly, and simple green synthesis of ZnO nanoparticles using Origanum vulgare extract. These nanoparticles are non-hazardous, environmentally friendly, and cheaper than other methods of biosynthesis. Ongoing research determines the role of phytochemicals in the fabrication and biosynthesis of ZnO NPs and their role in antibacterial activity and biomedical applications. Characterizations by fourier transform infrared spectroscopy (FTIR), diffuse reflectance UV-visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 111 publications
3
6
0
Order By: Relevance
“…In conclusion, treatment with Ag-Cu NPs inhibited biofilm development by 10–40%, with the most considerable inhibition observed at a dose of 50 µg/mL ( Figure 7 ). Our results are consistent with our previous studies in which ZnO NPs altered biofilm formation by C. violaceum [ 62 ]. Biofilm inhibition by metallic nanoparticles has been reported in many studies.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In conclusion, treatment with Ag-Cu NPs inhibited biofilm development by 10–40%, with the most considerable inhibition observed at a dose of 50 µg/mL ( Figure 7 ). Our results are consistent with our previous studies in which ZnO NPs altered biofilm formation by C. violaceum [ 62 ]. Biofilm inhibition by metallic nanoparticles has been reported in many studies.…”
Section: Resultssupporting
confidence: 94%
“…The MIC results showed that Ag-Cu NPs have potent antibacterial activity. The results follow previous studies in which synthesized ZnO NPs showed activity against an opportunistic pathogen, Chromobacterium violaceum [ 62 ].…”
Section: Resultssupporting
confidence: 90%
“…XRD analysis revealed the average size (nm) for the three samples from hydroethanolic extrats of Artemisia annua (A-@1 mgL -1 , B-@3 mgL -1 , C-@5 mgL -1 ) as 21.34, 24.00 and 24.71, respectively. The particle average sizes obtained for the synthesized ZnONPs were in agreement with the previous findings [50].…”
Section: Xrd Analysissupporting
confidence: 91%
“…4.A) as reported for Eichhornia crassipes leaf extract [51], H. rosa-sinensis [52], Calotropis gigantean [53] and Zingiber officinale [54]. The carbon peak observed could result from some carbon deposition during the calcination of the ZnONPs [50]. The purity, elemental composition and stoichiometry of the synthesized ZnONPs were performed by using EDS analysis.…”
Section: Sem-eds Analysismentioning
confidence: 77%
“…The biogenic ZnO NPs possess the ability to penetrate through the biofilm and act on the cells by bringing degradation in the genomic DNA and RNA content of the cell (Kamli et al, 2021 ). The biogenic ZnO NPs brought a marked reduction in the genomic DNA content of A. faecalis and P. gingivalis by 94.26 ± 1.09% and 96.23 ± 1.89%, respectively.…”
Section: Characterization Of the Green Synthesized Zno Npsmentioning
confidence: 99%